Phase 3 CLEAR study in patients with advanced renal cell carcinoma: outcomes in subgroups for the lenvatinib-plus-pembrolizumab and sunitinib arms - Grünwald, Viktor; Powles, Thomas; Eto, Masatoshi; Kopyltsov, Evgeny; Rha, Sun Young; Porta, Camillo; Motzer, Robert; Hutson, Thomas E.; Méndez-Vidal, María José; Hong, Sung-Hoo; Winquist, Eric; Goh, Jeffrey C.; et al. (Frontiers in Oncology, 2023)
The phase 3 CLEAR study demonstrated lenvatinib plus pembrolizumab significantly improved efficacy versus sunitinib in first-line patients with advanced renal cell carcinoma (RCC). Prognostic features including presence and/or site of baseline metastases, prior nephrectomy, and sarcomatoid features have been associated with disease and treatment success. This subsequent analysis explores outcomes in patients with or without specific prognostic features. Methods: In CLEAR, patients with clear cell RCC were randomly assigned (1:1:1) to receive either lenvatinib (20 mg/day) plus pembrolizumab (200 mg every 3 weeks), lenvatinib (18 mg/day) plus everolimus (5 mg/day), or sunitinib alone (50 mg/day, 4 weeks on, 2 weeks off). In this report, progression-free survival (PFS), overall survival (OS), and objective response rate (ORR) were all assessed in the lenvatinib-plus-pembrolizumab and the sunitinib arms, based on baseline features: lung metastases, bone metastases, liver metastases, prior nephrectomy, and sarcomatoid histology. Results: In all the assessed subgroups, median PFS was longer with lenvatinib plus pembrolizumab than with sunitinib treatment, notably among patients with baseline bone metastases (HR 0.33, 95% CI 0.21–0.52) and patients with sarcomatoid features (HR 0.39, 95% CI 0.18–0.84). Median OS favored lenvatinib plus pembrolizumab over sunitinib irrespective of metastatic lesions at baseline, prior nephrectomy, and sarcomatoid features. Of interest, among patients with baseline bone metastases the HR for survival was 0.50 (95% CI 0.30–0.83) and among patients with sarcomatoid features the HR for survival was 0.91 (95% CI 0.32–2.58); though for many groups, median OS was not reached. ORR also favored lenvatinib plus pembrolizumab over sunitinib across all subgroups; similarly, complete responses also followed this pattern. Conclusion: Efficacy outcomes improved following treatment with lenvatinib plus pembrolizumab versus sunitinib in patients with RCC—irrespective of the presence or absence of baseline lung metastases, baseline bone metastases, baseline liver metastases, prior nephrectomy, or sarcomatoid features. These findings corroborate those of the primary CLEAR study analysis in the overall population and support lenvatinib plus pembrolizumab as a standard of care in 1L advanced RCC.